Termografia digital por infravermelho do escroto e qualidade do sêmen em touros nelore (bos taurus indicus) - Ruediger, Felipe Rydygier de; Chacur, Marcelo George Mungai; Oba, Eunice [UNESP]; Amorim, Alcides Ramos [UNESP]; Souza, Camila Dutra de (Associacao Prudentina de Educacao e Cultura (APEC), 2014)
Aimed to study the relationship between scrotal temperature on semen quality by use of infrared thermography in Nelore bulls bred extensively. There were scrotal thermography and semen collection. Climatic data were collected by means of globe thermometer. The thermograms of the scrotum were obtained by digital infrared thermography. We carried out ejaculates through electroejaculation for analysis of quantitative and qualitative characteristics. For the data, we used analysis of variance and subsequently applied the Tukey test at 5%. (p <0.05) between animals for sperm vigor, sperm motility between animals and between crops, sperm concentration, total sperm and total viable sperm between groups, between harvests for the scrotum temperatures and climate data. It was concluded that the surface temperatures of the scrotum and climatic factors influence the quality of semen. Thermography is recommended as a complementary test in the evaluation of reproductive bulls.

Objetivou-se estudar a relação da temperatura do escroto sobre a qualidade seminal pelo uso da termografia por infravermelho em touros Nelore criados extensivamente. Realizaram-se termografia escrotal e colheita de sêmen. Os dados climáticos foram coletados por meio de globo termômetro. Os termogramas do escroto foram obtidos por meio de termografia digital de infravermelho. Efetuaram-se colheitas de sêmen, por meio de eletroejaculação para analise das características quantitativas e qualitativas. Para os dados, utilizou-se análise de variância e posteriormente aplicou-se o teste de Tukey a 5%. (p<0,05) entre animais para vigor espermático, motilidade espermática entre animais e entre colheitas, concentração espermática, espermatozoides totais e espermatozoides viáveis totais entre grupos, entre colheitas para as temperaturas do escroto e para os dados climáticos. Concluiu-se que as temperaturas da superfície do escroto e os fatores climáticos influenciaram na qualidade do sêmen. A termografia é recomendada como exame complementar na avaliação reprodutiva de touros.
Scrotum digital infrared thermography and semen quality in nelore bulls (bos taurus indicus)
Keywords: Climatic factors; Scrotal thermogram; Semen; Zebu bull; Fatores climáticos; Termograma escrotal; Touro zebu; Sêmen